Petrology of the Hornfels Contact Zone around the Hrossatungur Gabbro in the Eroded Hafnarfjall Central Volcano, W Iceland. - Alnethary, Moneer Fathel, 1978- (2018)
This study focusses on a hornfels zone on the southern side of the Hrossatungur gabbro, within the Hafnarfjall-Skarðsheiði central volcano, W-Iceland. The intrusion formed by repetitive injections of basaltic cone sheets, which were trapped at a lava-pyroclastite boundary within the Hafnarfjall caldera fillings. During contact metamorphism in response to the intrusion emplacement, a hornfels contact zone was created by a recrystallization process of previously hydrothermally altered basalt. Here, the hydrothermal alteration and chemical composition of minerals is closely studied to evaluate the development during the contact metamorphism event forming the hornfels around the gabbro. The hornfels mainly contains clinopyroxene compositions ranging widely from augite, salite, ferrosalite to hedenbergite in vesicle fillings, with minor orthopyroxene, while the groundmass clinopyroxene ranges from diopside, augite to salite. The plagioclase composition ranges from andesine, labradorite to bytownite and occasionally to anorthite within the vesicles and veins, while the groundmass plagioclase ranges from labradorite to anorthite. Other minerals found in the hornfels are iron-titanium oxides (magnetite, ilmenite and titano-magnetite), garnet, titanite, minor apatite and hornblende. The orthopyroxene include bronzite (Fs10-30), hypersthene (Fs30-50) and ferro-hypersthene (Fs50-70). Garnet compositional range goes mainly from andradite to about 20% grossular. Loss-on-ignition measurements reveal that the majority of samples located at the inner hornfels zone experience <1% LOI, while samples that show more extensive LOI are mostly situated at the outer hornfels zone. A comparison of the hornfels LOI with the LOI of Icelandic rocks in different alteration zones indicates that the hornfels rocks should have shown LOI >1% to <10% prior to the gabbro emplacement, which indicates that the water has been driven out of the rock by the replacement of hydrous minerals by non-hydrous minerals. For comparison, the ...